A platform of genetically engineered bacteria as vehicles for localized delivery of therapeutics: Toward applications for Crohn's disease. Issue 3 (23rd September 2018) - McKay, Ryan; Ghodasra, Monil; Schardt, John; Quan, David; Pottash, Alex Eli; Shang, Wu; Jay, Steven M.; Payne, Gregory F.; Chang, Matthew Wook; March, John C.; Bentley, William E.
Abstract: For therapies targeting diseases of the gastrointestinal tract, we and others envision probiotic bacteria that synthesize and excrete biotherapeutics at disease sites. Toward this goal, we have engineered commensal E. coli that selectively synthesize and secrete a model biotherapeutic in the presence of nitric oxide (NO), an intestinal biomarker for Crohn's disease (CD). This is accomplished by co‐expressing the pore forming protein TolAIII with the biologic, granulocyte macrophage‐colony stimulating factor (GM‐CSF). We have additionally engineered these bacteria to accumulate at sites of elevated NO by engineering their motility circuits and controlling pseudotaxis. Importantly, because we have focused on in vitro test beds, motility and biotherapeutics production are spatiotemporally characterized. Together, the targeted recognition, synthesis, and biomolecule delivery comprises a "smart" probiotics platform that may have utility in the treatment of CD. Further, this platform could be modified to accommodate other pursuits by swapping the promoter and therapeutic gene to reflect other disease biomarkers and treatments, respectively. Abstract : Here, we engineer commensal E. coli to overproduce and secrete a model biotherapeutic, granulocyte macrophage colony stimulating factor (GM‐CSF) in response to the Crohn's disease (CD) biomarker, nitric oxide. The GM‐CSF protein has shown utility as a therapy for CD, and thus the bacteria developed here may serve as a noninvasive method to localize drug delivery within the intestines of patients. Using the platform outlined in this work, replacing the biotherapeutic gene with another of interest can produce engineered probiotics that secrete therapies for other diseases.